2003
DOI: 10.1046/j.1360-0443.2003.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use by university students, Lebanon, 2001

Abstract: The authors advocate a collaborative effort to alleviate the consequences of smoking among university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
109
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 18 publications
22
109
2
5
Order By: Relevance
“…Other factors that attract WP smokers, especially adolescents, are its aromatic and condensed smoke, attractive pipe design, availability, inexpensive tobacco, and social acceptance because of traditional associations and it being less stigmatized than cigarette smoking [22]. WP smoking is a new challenge for global public health efforts [23], and recent studies have shown that WP smoke is more harmful than cigarette smoke, because one session of WP smoking expose it's users to a larger amount of smoke and higher level of tobacco toxicants such as tar, carbon monoxide, nicotine, and arsenic compared with one cigarette [24][25][26][27][28][29].WP smoking is considered to be associated with lung cancer, esophageal cancer, low birth weight, periodontal diseases, and pulmonary dysfunction [30].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that attract WP smokers, especially adolescents, are its aromatic and condensed smoke, attractive pipe design, availability, inexpensive tobacco, and social acceptance because of traditional associations and it being less stigmatized than cigarette smoking [22]. WP smoking is a new challenge for global public health efforts [23], and recent studies have shown that WP smoke is more harmful than cigarette smoke, because one session of WP smoking expose it's users to a larger amount of smoke and higher level of tobacco toxicants such as tar, carbon monoxide, nicotine, and arsenic compared with one cigarette [24][25][26][27][28][29].WP smoking is considered to be associated with lung cancer, esophageal cancer, low birth weight, periodontal diseases, and pulmonary dysfunction [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to Poyrazoglu et al (2010), residence, economic status of the family, and with whom students live have no significant effect on the prevalence rate. In contrast, Tamim et al (2003) and Anjum et al (2008) reported that the highest percentage of shisha smoking occurred among college students in a higher socioeconomic group.…”
Section: Discussionmentioning
confidence: 87%
“…The popularity of the narghile waterpipe, also referred to as hookah, shisha or hubble-bubble has increased tremendously during the past few decades (Tamim et al, 2003;Akl, 2011) and has spread beyond the bounds of Arab countries to other parts of the world, including Europe and America Jarrett et al, 2012;Shihadeh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%